One new piperazinedione isolated from a mangrove-derived fungus Aspergillus niger JX-5. Issue 9 (3rd May 2022) - Bai, Meng; Wang, Yue; Liu, Ting; Lian, Yu-Xing; Bai, Qi-Qi; Song, Xiao-Ping; Han, Chang-Ri; Zheng, Cai-Juan; Chen, Guang-Ying
Abstract: One new piperazinedione derivative, nigerpiperazine A (1 ), along with six known compounds (2–7 ) were isolated from the fungus Aspergillus niger JX-5 from mangrove Ceriops tagal . Nigerpiperazine A (1 ) was elucidated by spectroscopic analyses and 13 C NMR chemical shift calculations, compounds 4 and 5 were determined by X-ray and the CD spectra. The absolute configuration of 4 was identified by X-ray for the first time. Compounds 1 and 4 showed inhibitory activities against Helicoverpa armigera Hubner with the IC50 values of 200 and 100 µg/mL, respectively. Graphical Abstract: